Concrete in marine environment : proceedings, second international conference, St. Andrews by-the-Sea, Canada, 1988 - Malhotra, V. M.; American Concrete Institute; Canada. Centre for Mineral and Energy Technology; International Conference on Performance of Concrete in Marine Environment (2nd : 1980 : St. Andrews, N.B.) (Detroit : ACI, 1988)
09